Recurso natural, organização espacial e ordenamento territorial: mineração e degradação de terras na depressão interplanáltica semiárida do Alto Coreaú (CE) - Albuquerque, Francisco Nataniel Batista de [UNESP] (2015)
The creation of the Ubajara national park (1959) and the installation of the cement plant of the Votorantim group (1964) in the depressão interplanáltica semiárida do Alto Coreaú (DISAC), whose area of 979 km2 is located in the northwestern portion of the State of Ceará, are configured as large timeframes in the appropriation of natural resources in the region. Given the above, the research aims to investigate the relationship between the appropriation of natural limestone resource, whether in the form of rock for the production of lime and cement (landscape element) or geomorphological features for tourism (landscape aspect) the spatial organization and the degradation of semi-arid lands in geosystem of DISAC. The methodology set out an integrated analysis of the social and natural systems operating in 03 different spatial scales: geosystem (carbonate formation DISAC), geofácie (Aroeiras limestone field) and the geótopo (rock outcrops of Aroeiras field), and the concept of natural resource as a link of integration between the systemic and dialectical paradigms present in geosystemic conceptions of Sotchava (1977) and Bertrand (1968) and the Theory of Two Circuits of Urban Economy Santos (1979), in order to understand the regional spatial organization and propose territorial management measures (EGLERet al, 2012). Among the results is a theoretical and methodological proposal of a complementary rather than antagonistic dialogue of systemic and dialectical paradigms, from terminological adjustments, scalar and themes, offered by the concept of natural resource. In the empirical field, there was the influence of Ubajara national park in the spatial organization of geosystem, from environmental restrictions on Frecheirinha field leading to the decline of the mining activity of subsistence and, instead, the consolidation of an intimate fashion hub in namesake city and the revelation of the mineral by large mining Aroeiras field...